Moisture Susceptibility of Sustainable Warm Mix Asphalt - Amjad H. Albayati; Hasan M. Al-Mosawe; Abbas A. Allawi; Nazar Oukaili (Advances in Civil Engineering)
Sustainable pavements are pavements that meet the requirements of present generation without influencing the capability of the future generation to meet their needs. One of the problems of the warm mix asphalt is that it has low resistance to moisture damage; therefore, the aim of this research paper is to study the possibility of producing more durable warm mixes against the moisture damage with the use of recycled concrete aggregate (RCA) which has not been studied before. Six replacement rates (0, 20, 40, 60, 80, and 100%) for the coarse version aggregate (VA) with RCA were studied. The Marshall mix design method was used to determine the optimum asphalt cement content for each replacement rate. Thereafter, specimens with the optimum asphalt cement content were prepared and tested in the indirect tension test to evaluate their moisture susceptibility. The results revealed that the mixes with higher percentage of RCA possess higher optimum asphalt content. Moreover, an improvement of 13 and 28% in Marshall stability and tensile strength ratio (TSR), respectively, was obtained in case that the VA was entirely replaced by the RCA.